INVESTIGATION OF BIOLOGICAL PROPERTY FEATURES VARIABILITY OF CANDIDA FAMILY YEAST-LIKE FUNGI - Zumarad, Allaberganova (PT. Antis International Publisher, 2025)
Objective: Yeast-like fungi of the Candida genus are opportunistic pathogens implicated in candidiasis, yet biological variability—particularly in colony morphology and proteolytic properties—remains underexplored beyond Candida albicans, especially across strain origins, culture passages, and storage conditions. Method: This study investigated the morphological and proteolytic characteristics of Candida spp. from both hospital and collection strains, assessing variability under controlled passage conditions. Evaluations were conducted using a rice bran-based medium and a standardized scale for growth assessment. Results: The study identified distinct colony morphotypes—typical S, atypical K, and rare R forms—whose distribution varied with passage number and storage duration. Notably, collection strains exhibited a significant decline in proteolytic activity by the third passage, while hospital strains showed reduced enzymatic activity from the initial passage. Novelty: This research provides new insights into the phenotypic plasticity of Candida strains, emphasizing the diagnostic relevance of passage tracking. It also introduces a practical and accessible method for evaluating growth characteristics using rice bran-based media, contributing to improved diagnostic accuracy, treatment strategies, and epidemiological monitoring in clinical mycology.